A Analysis of Observation Results Preventing Children's / Adventures' Delinquency in The Environment Around Semarang State University - Nisaa Hamidah Nisaa Hamidah (International Journal of Educational Technology Research, 2023)
Research This aim for (1) as effort For ward off mischief child / adolescent in a way wise , precise , and efficient which is topic the discussion presented in study this (2) in order to obtain addition input for K produce increasing therapy _ accurate for educators _ especially , leaders public generally in develop source Power quality human being through humanities ( sciences For advance human ) so reach true humanity . _ Study This is study descriptive qualitative . Research setting it's in the environment around UNNES, subject study This is children / adolescents in the environment around UNNES. Tools or instrument study researcher role active in obtaining data in the field . Data collection techniques used covers observation and documentation.